Fluid Balance in the Critically Ill Child Section: “How Bad Is Fluid in Neonates?” - Rutledge, Austin; Murphy, Heidi J.; Harer, Matthew W.; Jetton, Jennifer G. (Frontiers in Pediatrics, 2021)
Fluid overload (FO) in neonates is understudied, and its management requires nuanced care and an understanding of the complexity of neonatal fluid dynamics. Recent studies suggest neonates are susceptible to developing FO, and neonatal fluid balance is impacted by multiple factors including functional renal immaturity in the newborn period, physiologic postnatal diuresis and weight loss, and pathologies that require fluid administration. FO also has a deleterious impact on other organ systems, particularly the lung, and appears to impact survival. However, assessing fluid balance in the postnatal period can be challenging, particularly in extremely low birthweight infants (ELBWs), given the confounding role of maternal serum creatinine (Scr), physiologic weight changes, insensible losses that can be difficult to quantify, and difficulty in obtaining accurate intake and output measurements given mixed diaper output. Although significant FO may be an indication for kidney replacement therapy (KRT) in older children and adults, KRT may not be technically feasible in the smallest infants and much remains to be learned about optimal KRT utilization in neonates. This article, though not a meta-analysis or systematic review, presents a comprehensive review of the current evidence describing the effects of FO on outcomes in neonates and highlights areas where additional research is needed.